The Influence of Service Quality, Customer Trust and Customer Satisfaction on Customer Loyalty for Laundry Services - Rieska Ramdhanty, Azharly; Muslim, Muslim (International Journal of Economics, Management and Accounting (IJEMA), 2024)
The aim of this research is to evaluate the impact of service quality, customer trust and customer satisfaction on customer loyalty to Laundry 88 services. The research method used is a quantitative method. The population in this study includes all customers or consumers who have used Laundry 88 services. The sampling technique was carried out using purposive sampling, with a total sample of 84 respondents. The main data source used in this research is primary data. Data collection was carried out through distributing questionnaires online using Google Form, and data analysis using Multiple Linear Regression. The research results show that service quality has a significant influence on customer loyalty, while customer trust has a positive and significant influence on customer loyalty, and customer satisfaction also has a positive and significant influence on customer loyalty.